The Supporting factors for javan langur rehabilitation management (Trachypithecus auratus E. Geoffroy, 1812) In Javan Langur Center Batu, East Java - Andi Nurul Ananda; Nyoto Santoso; Jarwadi B Hernowo (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2022)
The population of the Javan langur (Trachypithecus auratus) is currently decreasing, so the threat to the preservation of the Javan langur requires conservation efforts that are beneficial for conservation in nature.One of the conservation efforts is carried out ex-situ, such as the one at the research station at the Javan Langur Center. This study aims to determine the Rehabilitation management of Javan langurs at the Javan Langur Center. The method used in this research is the interview, field observation, and literaturestudy. The use of strategic factor analysis (SWOT) is carried out in the management of Javan Langur rehabilitation which includes analysis of internal factors and external factors. The first rehabilitation management, namely the development strategy at the research site, is carried out through a rehabilitation program strategy. The second utilizes and maintains good support from the government. Third, utilize experienced human resources. Fourth, increase the number of health workers who are still lacking. Fifth,improve the quality and quantity of facilities and infrastructure. Sixth, add experienced human resources. Seventh, improving the quality and quantity of facilities at the Javan Langur Center.